Pengaruh Kualitas Produk Dan Penerapan Nilai Islam Terhadap Kepuasan Nasabah (Studi Pada BMT Al-Hijrah Bukittinggi) - Adella, Sinky; Dila Anggraini; Anwar Sholihin (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Product Quality and Application of Islamic Values can affect customer satisfaction, because customer satisfaction can be used as a marketing strategy design in Financial Institutions. The purpose of this study is to measure the effect of product quality and the application of Islamic values on customer satisfaction and which of these two variables has more influence on customer satisfaction at BMT Al-Hijrah Bukittinggi. In this study, the data collection method used was primary data or by distributing questionnaires filled out by BMT Al-Hijrah Bukittinggi customers. The analytical technique used in this research is to use the data normality test, validity and reliability test, and hypothesis testing. From the results of data analysis, it can be concluded that the product quality variable has a significant effect on customer satisfaction with a significant level of 0.000, then the variable application of Islamic values to customer satisfaction at BMT Al-Hijrah Bukittinggi with a significant level of 0.000.